ORGANISASI DAN LINGKUNGANNYA - Soliha, Euis; Maharani, Kurnia (Benefit, 2011)
In this time every organizations challenge ever greater in developing its capacities. Organizations will do not want to deal with environment which always change. Only organizations Â fit with the environment, they will survive. The way of to increase power with acquition resources and copying uncertainty